Water and Sanitation for All in Tunisia : A Realistic Objective - World Bank (World Bank, Washington, DC, 2018)
In recent decades, Tunisia has made remarkable progress in reducing poverty and increasing access to water supply, sanitation, and hygiene (WASH) services. More than 4 million people in Tunisia have gained access to improved sanitation between 1990 and 2015, and 4 million have gained access to water. This is a significant accomplishment, considering that Tunisia is currently home to 11 million people, 33 percent of whom live in rural areas. Despite this progress, however, around 250,000 people in Tunisia still rely on unimproved drinking water from mostly unprotected wells and springs; of the 900,000 people who use unimproved sanitation, about half use shared latrines, and the other half use mostly unimproved latrines. There are also substantial imbalances in terms of water-resource distribution between the better endowed North and the semi-arid South. If left unaddressed, deficiencies could become more severe in the coming years. Tunisia is a water-scarce country, and water supply security challenges are predicted to be exacerbated by climate change in the coming years. Opportunities for improvement are analyzed and condensed into five clear recommendations for the way forward for the WASH sector in Tunisia.